Southeast Asia in search of an ASEAN community insights from the former ASEAN secretary-general - Severino, Rodolfo (Institute of Southeast Asian Studies, 2006)
"... This volume reappraises the organization from the inside, through controversial or perplexing issues such as the "ASEAN Way", the accession of the new members, including Myanmar, the principle of "non-interference", regional security, regional economic integration, the haze and SARS, and ASEAN's future"--ISEAS Publications Unit.